ANALYSIS OF YOGYAKARTA EARTHQUAKE AFTERSHOCK RELOCATION IN THE MIDDLE PERIOD OF JUNE 2006 USING DOUBLE-DIFFERENCE - Yusvandi Chand, Vicky
Yogyakarta Earthquake 2006 is the type of tectonic earthquake with the impact of damage is great for Yogyakarta and surrounding areas. USGS noted the earthquake occured at 05:53:58 AM, the epicenter position was 7.97°LS and 110.44°BT, a depth about 10 km, and a magnitude of 6,3 Mw. The first assumption about the main cause of Yogyakarta Earthquake is the movement of Opak River Fault, a sinistral fault that extends from Parangtritis area to the east of Yogyakarta. However, several subsequent studies have found that there is another fault that could be the real main cause of the Yogyakarta Earthquake. Located about 10 – 20 km to the east and parallel with Opak Fault. Since June – August 2006 there are 2000 aftershock wave of Yogyakarta Earthquake which recorded by seismic stations. By analizing dispersion of aftershock, the fault mechanisms that occur under the earth’s surface could be studied. The initial process is picking the arrival time of P and S waves of the aftershock data set. After that, the next step is the hypocenter determination using Hypoellipse program which based on Geiger’s Principle. From the initial hypocenter plotting, there are 738 aftershock events in the period of mid-June 2006. It shows similar results with some previous studies. The next step is relocation which applies the doubl-difference method. Relocation using cross-correlation data set obtained by waveform cross-correlation method resulted a better cluster grouping and formed a more stight line. There are five clusters formed by these processes which are separated by distance. The main cluster is the aftershock distribution that forms a lineage of fault lines with the trends is southwest – northeast. The strike orientation is 42°NE, dip 82°, and 8 km to the east of the Opak Fault. These result reinforce the suspicion that the Opak Fault is not the main reason that caused The 2006 Yogyakarta Earthquake. In addition, analysis of the main cluster and 2nd cluster forms a structure of graben that has strike alignment with the Opak Fault.